Effect of recombinant human growth hormone on glucose metabolism in children with growth hormone deficiency - Liang, Li (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2006)
OBJECTIVE: Numerous studies in children with growth hormone deficiency (GHD) show that recombinant human growth hormone (rhGH) treatment results in significant catch-up growth, but some papers reported that the children who underwent rhGH therapy might be at increased risk of diabetes. The aim of this study was to investigate the effects of rhGH treatment on blood glucose and insulin metabolism in children with GHD and the relationship between growth hormone (GH) and glucose homeostasis